PERHITUNGAN PREMI ASURANSI JIWA DWIGUNA PASUTRI SEBAGAI PENERAPAN PEMBELAJARAN MATEMATIKA EKONOMI - irma fauziah (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2013)
In learning mathematical economics, the calculation of life insurance premiums is a matter concerning the application of a combination of compound interest, probability, differential and integral. Life insurance with multilife concept is the one of ap- plied in actuarial mathematics. A functions, in the actuarial cal- culation, related to death sequence in multilife concept is called as contingent function. Usage that function in calculation of insurance premium will assist the insurer in giving the benet precisely.Contingent probabilities are resulted by multiplication be- tween the force of mortality of life in the last sequence of death which have been determined and probabilities of life all family member in multilife status. Insurance formulation is obtained by mutiplying this probabilities with vt discount factor and they are integrated by using the assumption of a uniform distribution of death throughout the year of age.